Activation of compensatory pathways via Rac2 in the absence of the Cdc42 effector Wiskott-Aldrich syndrome protein in Dendritic cells - Baptista, Marisa A. P. (Small GTPases, 2017)
There is extensive crosstalk between different Rho GTPases, including Cdc42, Rac1, and Rac2, and they can activate or inhibit the activity of each other. Dendritic cells express both Rac1 and Rac2. Due to posttranslational modification of lipid anchors, Rac1 localizes mainly to the plasma membrane whereas Rac2 localizes to the phagosomal membrane where it assembles the NADPH complex. Our recent study of primary immunodeficiency disease caused by mutations in the Cdc42 effector Wiskott-Aldrich syndrome protein (WASp) has shed light on the compensatory mechanisms between Rho GTPases and their effector proteins. WASp-deficient dendritic cells have increased localization and activity of Rac2 to the phagosomal membrane and this allows antigen to be presented on MHC class I molecules to activate cytotoxic CD8(+) T cells. This study reveals an intricate balance between Rac2 and WASp signaling pathways and provides an example of compensatory pathways in cells devoid of the Cdc42 effector WASp.